2007
DOI: 10.1007/s10567-007-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Do the Predictors of Child Conduct Problems Vary by High- and Low-Levels of Socioeconomic and Neighborhood Risk?

Abstract: This review seeks to examine whether the existing literature on child conduct problems (CP) supports the notion that certain CP risk factors vary in their importance across disadvantaged and better-off environments. Disadvantaged environments are represented by socioeconomic and/or neighborhood risk (SN risk) in this review. Three types of studies were reviewed: behavioral genetic studies that compare the importance of genetic and environmental influences on CP for youth from poor homes and/or disadvantaged co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 192 publications
(209 reference statements)
3
66
1
2
Order By: Relevance
“…The child factors were more influential on EB at T2 than the proximal family factors, with 48% and 30% respectively of variance explained. These results are in line with the idea that high levels of deleterious environmental factors such as harsh parenting or high disorganization in attachment are relatively rare in low contextual risk families and that therefore, individual risk factors contribute more than proximal family factors to the development of later EB (Bronfenbrenner & Ceci, 1994;Lanza et al, 2010;Schonberg & Shaw, 2007). In line with this assumption, the influence of both parenting and attachment was no longer significant in the model where all of the child and the proximal family factors were considered as predictors.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The child factors were more influential on EB at T2 than the proximal family factors, with 48% and 30% respectively of variance explained. These results are in line with the idea that high levels of deleterious environmental factors such as harsh parenting or high disorganization in attachment are relatively rare in low contextual risk families and that therefore, individual risk factors contribute more than proximal family factors to the development of later EB (Bronfenbrenner & Ceci, 1994;Lanza et al, 2010;Schonberg & Shaw, 2007). In line with this assumption, the influence of both parenting and attachment was no longer significant in the model where all of the child and the proximal family factors were considered as predictors.…”
Section: Discussionsupporting
confidence: 82%
“…child and family, but the predictive power of these was shown to be different. The influence of the child factors was higher than the influence of the family ones, and the deleterious level of the proximal family factors was found to be relatively low (Schonberg & Shaw, 2007). In line with these conclusions, two preferable pathways to pathological EB could be suggested for children incurring no distal risk.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…For instance, research has found that parental monitoring matters more in high -risk environments than low -risk ones (Schonberg & Shaw, 2007 ), that parental monitoring decreases as children age (McDowell & Parke, 2009 ), and that parental monitoring has varying infl uences on peer relationships (Mounts, 2001 ). Thus, the impact of parenting practices on peer interactions may be accentuated or attenuated by environmental risk at different developmental ages.…”
Section: Parent and Peer Relations Within The Broader Social Contextmentioning
confidence: 99%
“…Schonberg & Shaw 2007). Published findings regarding associations between parents' marital status, immigration, and child behaviour problems are rare, and fewer studies still have reported on these associations in early childhood (Javo et al, 2004).…”
Section: Socio-economic Statusmentioning
confidence: 99%